2016
DOI: 10.21608/jsrs.2016.15468
|View full text |Cite
|
Sign up to set email alerts
|

Floristic and Vegetation Study on the Main Weed Communities Associated with Wheat (Triticum aestivum L.) Crop

Abstract: The present study aims at studying the floristic features and community types of the main weed species associated with wheat crop in Menofia Province, Egypt. Sixty stands (each 10 × 10 m) were randomly selected in five wheat farms for monthly determining the cover of weed species along the growing season of wheat. Twenty nine species belonging to 28 genera and 17 families were recorded associated with wheat crop. The most dominant families were Poaceae, Brassicaceae and Fabaceae. Annual weeds were represented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
1
2
1
Order By: Relevance
“…Where, these families constitute the bulk of the flora of the study area. This result is similar to those in Dakahlia-Damietta coastal region (Mashaly, 1987), the wastelands the Zagazig governorate (Abd El-Fattah et al, 1992), Kafr ElSheikh province (Shalaby, 1995), the Nile Delta region (Shehata and Galal, 2014) and in Al Kalubya, Mynufia and Buhayra (Khalafallah et al, 2016b). Of 141 species associated to M. parviflora, 88 were annuals and 55 species were perennials.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Where, these families constitute the bulk of the flora of the study area. This result is similar to those in Dakahlia-Damietta coastal region (Mashaly, 1987), the wastelands the Zagazig governorate (Abd El-Fattah et al, 1992), Kafr ElSheikh province (Shalaby, 1995), the Nile Delta region (Shehata and Galal, 2014) and in Al Kalubya, Mynufia and Buhayra (Khalafallah et al, 2016b). Of 141 species associated to M. parviflora, 88 were annuals and 55 species were perennials.…”
Section: Discussionsupporting
confidence: 78%
“…Zohary (1973) referred to the dominance of interregional species (bi-, tri-and pluri-regional) over mono-regional ones to the presence of inter-zonal habitats, such as anthropogenic or hydro-, halo-and psammophilous sites. The present result isn't in consistent with the results of Suliman et al (2016)and Khalafallah et al (2016a and2016b), where they found that mono-regional species were the dominant elements in maize and wheat crops in Middle Delta and Opuntia ficus indica orchards. On the other hand, Mashaly (1987) recorded 50% of the species in the Deltaic sector are Mediterranean, 32% are pluri-regionals, and 8% are Saharo-Sindian elements.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations